Local immune cell infiltration in cutaneous acute graft versus host disease - Rachel Sennett, MD, PhD; Burhan M. Jama, BS; Brian Hinds, MD; Dimitrios Tzachanis, MD, PhD; Gerald P. Morris, MD, PhD; Amanda F. Marsch, MD (Wolters Kluwer, 2020)
Background: Hematopoietic stem cell transplant is a crucial intervention to definitively treat many hematopoietic malignancies, but it carries great risks of morbidity and mortality often associated with graft-versus-host disease (GVHD). Acute and chronic GVHD are distinct entities, defined by a combination of historical, clinical, and pathologic data, but both are generally thought to stem from self-propagating aberrantly activated immune cells inflicting end organ damage, with the potential to cause significant illness or even death. Event-free survival rates after hematopoietic stem cell transplant continue to improve each year, but GVHD remains a major hurdle in improving the efficacy and safety of transplant. Objective: Recent studies demonstrating tissue-specific immune effector phenotypes underscore the need for a deeper understanding of the cellular and molecular pathways driving the destruction of target tissues in patients with acute GVHD. Methods: Samples were collected from lesional and unaffected skin in five patients with acute cutaneous GHVD. Fresh tissue was processed for fluorescence-activated cell sorting and analysis of macrophages and lymphocytes. Results: The percentage of lymphocytes and macrophages as a representation of total cells varied among patients and was not always consistent between lesional and unaffected sites. The heterogeneity in immune cell profiling observed in patients in this study could reflect the diverse demographics, conditioning, and transplant conditions of each individual. Conclusion: This study provides initial insight into the underlying molecular mechanisms of cutaneous GVHD progression and paves the way for additional studies to examine the cellular and molecular landscape in greater detail.